Effectiveness of ProlotherapyInjection in Elderly Patients with Knee Osteoarthritis: A Double-Blind Randomized Controlled Trial - Faizal Muhammad; Afifah Syifaul Ummah; Farida Aisyah; Isa Ridwan; Yulie Erida Nur Rahmawati (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND : Knee osteoarthritis (OA) is a painful chronic disease in elderly population. Research has shown that prolotherapy is an effective pain-relieving treatment, particularly when used in combination with other therapies. AIMS :  To evaluate the effectiveness of prolotherapy for knee OA based on The Western Ontario McMaster University OA Index (WOMAC) composite score (100 points), Knee Pain Scale, and self-reported satisfaction. We performed a randomized-controlled trial (RCT) with a double-blinded approach. METHOD: An injection saline, 10% dextrose (D10) prolotherapy, or at-home knee exercise was administered to twenty-seven elderly patients (≥60 years old) experiencing painful knee OA for at least three months. Extra- and intra-articular injections were administered at weeks 1, 4, and 7, with follow-up at weeks 11 and 15. Exercise group received in-person training and an exercise guidebook. WOMAC composite score (100 points), Knee Pain Scale, and self-reported satisfaction evaluated the outcomes. The results were considered statistically significant if p < 0.05. RESULT:  There are no significant difference in baseline among groups. At 21 weeks, all groups exhibited improved composite WOMAC scores (p <0.02) compared to baseline. After adjusting for age, sex, and body mass index, D10 prolotherapy showed a significant WOMAC score improvement at 21 weeks (p <0.04) compared to saline and exercise (score change: 16.2 ± 4.4 vs. 8.5 ± 4.3, and 9.1 ± 3.2, respectively), surpassing the minimal clinically significant difference based on WOMAC. Self-reported satisfaction with D10 prolotherapy was high without reported adverse effects. CONCLUSION: When compared to saline injections and at-home exercises, D10 prolotherapy resulted in a clinically significant sustained improvement in pain, function, and stiffness scores for knee OA in elderly.